2003
DOI: 10.1029/2003wr002185
|View full text |Cite
|
Sign up to set email alerts
|

Water table waves in an unconfined aquifer: Experiments and modeling

Abstract: [1] Comprehensive measurements are presented of the piezometric head in an unconfined aquifer during steady, simple harmonic oscillations driven by a hydrostatic clear water reservoir through a vertical interface. The results are analyzed and used to test existing hydrostatic and nonhydrostatic, small-amplitude theories along with capillary fringe effects. As expected, the amplitude of the water table wave decays exponentially. However, the decay rates and phase lags indicate the influence of both vertical flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 16 publications
3
53
0
Order By: Relevance
“…The present data however has highlighted significant limitations in this approach, particularly in the high-frequency limit. Limitations of the model when applied to the 2D case of a propagating water table wave have also been identified [Cartwright et al, 2003[Cartwright et al, , 2004. As such it is suggested that further development of the problem be directed toward improving the understanding of the processes involved in the coupling of the saturated zone with the capillary fringe.…”
Section: Influence Of Proximity To the Sand Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The present data however has highlighted significant limitations in this approach, particularly in the high-frequency limit. Limitations of the model when applied to the 2D case of a propagating water table wave have also been identified [Cartwright et al, 2003[Cartwright et al, , 2004. As such it is suggested that further development of the problem be directed toward improving the understanding of the processes involved in the coupling of the saturated zone with the capillary fringe.…”
Section: Influence Of Proximity To the Sand Surfacementioning
confidence: 99%
“…It does however provide a simple, and computationally efficient way to account for its influence on the nature of water table fluctuations and is easily applied to existing dispersion relation theories to describe water table attenuation [e.g., Nielsen and Turner, 2000;Cartwright et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Salt water was pumped from a saltwater tank into the reservoir via a variable height overflow (VHO) column, which generated the tidal fluctuations [Cartwright et al, 2003]. The grain size distribution of the sand used in the experiments is relatively uniform with d 50 5 0.24 mm and d 90 /d 10 5 2.86.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…During the wash, a handheld multiparameter meter (YSI Professional Plus) was used to monitor the pore water salinity. Afterward, the sand was put into the flume and settled by gravity in prefilled salt water of 15 ppt to ensure that the initial pore water salinity was uniform and to avoid trapped air [Cartwright et al, 2003]. …”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Lanyon et al, 1982;Nielsen, 1990;Turner et al, 1997;Raubenheimer et al, 1999), laboratory experiments (e.g. Parlange et al, 1984;Nielsen et al, 1997;Boufadel et al, 1998;Ataie-Ashtiani et al, 1999;Cartwright et al, 2003), analytical modelling (e.g. Parlange et al, 1984;Barry et al, 1996;Li et al , 2000;Kong et al, 2013); and numerical modelling (e.g.…”
Section: Introductionmentioning
confidence: 99%